2022
DOI: 10.3390/nu14132765
|View full text |Cite
|
Sign up to set email alerts
|

Different Dose of Sucrose Consumption Divergently Influences Gut Microbiota and PPAR-γ/MAPK/NF-κB Pathway in DSS-Induced Colitis Mice

Abstract: Sugar reduction and sugar control are advocated and gaining popularity around the world. Sucrose, as the widely consumed ingredient in our daily diet, has been reported a relation to gastrointestinal diseases. However, the role of sucrose in inflammatory bowel disease remains controversial. Hence, our study aimed to elucidate the potential role of three doses of sucrose on DSS-induced colitis in C57BL/6 mice and the underlying mechanisms. The results showed that low-dose sucrose intervention alleviated colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…A correlation between SCFA levels and the abundance of Faecalibaculum, Romboutsia, Bacteroides, and Turicibacter were found in rats. Faecalibaculum was the most strongly positively correlated with the levels of SCFA levels, which are well known as the endogenous ligands of PPARγ, and crucially together with increasing PPARγ expression, promoting the PPARγ/MAPK/NF-κB signaling pathway connected with the metabolism and immune system (Zhang et al, 2022).…”
Section: Shared Metabolic Pathways Associated With Ncpb and Depressiv...mentioning
confidence: 99%
“…A correlation between SCFA levels and the abundance of Faecalibaculum, Romboutsia, Bacteroides, and Turicibacter were found in rats. Faecalibaculum was the most strongly positively correlated with the levels of SCFA levels, which are well known as the endogenous ligands of PPARγ, and crucially together with increasing PPARγ expression, promoting the PPARγ/MAPK/NF-κB signaling pathway connected with the metabolism and immune system (Zhang et al, 2022).…”
Section: Shared Metabolic Pathways Associated With Ncpb and Depressiv...mentioning
confidence: 99%
“…The identification of mammalian PPARγ as a mifepristone target is of particular interest. PPARγ is a central regulator of lipid and glucose metabolism [ 9 ], and acts as an anti-inflammatory regulator in the gut [ 10 , 11 ], and as a regulator of lipid metabolism adaptation during pregnancy [ 12 ]. Thiazolidinedione drugs, including pioglitazone and rosiglitazone, have been used to treat diabetes based on their ability activate PPARγ [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the compound−target network analysis indicated that astragalin, 2″-(6-acetylglucosyl)astragalin, sucrose, and narcissin were identified as the primary components responsible for the anti-inflammatory properties exhibited by SP extract. Previous studies have verified that both astragalin and low dose of sucrose could effectively alleviate the severity of colitis in mice 33,34 and also reported that astragalin and narcissin have potent anti-inflammatory effects against alveolar inflammation, osteoarthritis, and neuroinflammation by down-regulating MAPK and/or PI3K/Akt signaling pathways. 35−38 Taken together, these findings collectively indicate that SP extract possesses the ability to alleviate DSS-induced colonic 39 has been previously reported to reduce hepatocyte apoptosis and combat concanavin A-induced liver injury in a CD95dependent manner.…”
Section: ■ Discussionmentioning
confidence: 85%